A Statistical Investigation of Factors Influencing the Magnetotail Twist at Mars - Gina A. DiBraccio; Norberto Romanelli; Charles F. Bowers; Jacob R. Gruesbeck; Jasper S. Halekas; Suranga Ruhunusiri; Tristan Weber; Jared R. Espley; Shaosui Xu; Janet G. Luhmann; Yuki Harada; Eduard Dubinin; et al. (Geophysical Research Letters)
Abstract The Martian magnetotail exhibits a highly twisted configuration, shifting in response to changes in polarity of the interplanetary magnetic field's (IMF) dawn‐dusk (BY) component. Here, we analyze ∼6000 MAVEN orbits to quantify the degree of magnetotail twisting (θTwist) and assess variations as a function of (a) strong planetary crustal field location, (b) Mars season, and (c) downtail distance. The results demonstrate that θTwist is larger for a duskward (+BY) IMF orientation a majority of the time. This preference is likely due to the local orientation of crustal magnetic fields across the surface of Mars, where a +BY IMF orientation presents ideal conditions for magnetic reconnection to occur. Additionally, we observe an increase in θTwist with downtail distance, similar to Earth's magnetotail. These findings suggest that coupling between the IMF and moderate‐to‐weak crustal field regions may play a major role in determining the magnetospheric structure at Mars.